Prototype of EMR Information System for Primary Clinics According to Health Big Data Needs - Astuti, Nina Dwi; Wijayanta, Setya; Fahyudi, Asharul; Naryanti, Indah (Poltekkes Kemenkes Semarang, 2024)
Digital Health Transformation requires health facilities to develop Electronic Medical Records (EMR) according to predetermined data standards. This research aims to develop a prototype of the Semarang Ministry of Health Polytechnic Primary Clinic RME which can be integrated with the SATUSEHAT portal. The EMR Primary Clinic prototype is prepared by analyzing system needs and designing prototypes to build a prototype. The subjects of the study were doctors, dentists, and administrative officers. The object of the study was the EMR Primary Clinic of Health Polytechnic of Semarang. The prototype results are compiled simple design but can include standard interoperability of data. Registration data includes all data standards in KMK 1423 of 2022. The EMR prototype can record all the clinical data and administrative data needed in the EMR. The test results show that this EMR prototype can accommodate the needs of primary care clinics and meet the data standards set by